PENGARUH PENERAPAN METODE PEMBELAJARAN INKUIRI DIPADU KETERAMPILAN PROSES SAINS TERHADAP HASIL BELAJAR BIOLOGI MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN - Hilda Karim; Andi Asmawati Azis; Nursyahida A; Saparuddin (Jurnal Biogenerasi, 2021)
The study aims to find a description of the result of studying the biology of learners with the application of methods of inquiry learning coupled with the sciences processes skills of studying the biology of participants on the structural materials and function of plant tissue. This type of research is an experimental quasi involving two groups where one group as an experimental group and the other group as a control group. This research population is the learning group of students class XI MIPA MAN 1 Polewali Mandar and selected two calsses purposively sampling. The two classes selected are class XI MIPA 2 as experiment group and class XI MIPA 3 as control class. The data of research are collected by results of study tests before and after the study are the analyzed using descriptive and inferential statistics and advanced scientific observation sheets that are analyzed using descriptive statistic. In this research, four indicators of the scientific process of observation, classifying, communicating and concluding. The result show that the four indicator have changed in each meeting with an average of all aspects per meeting, namely the first meeting of 65,44% is in the enough category, the second meeting is 72,22% is in the enough category, and the third meeting is 85,55% in the good category. Result suggest that the method of inquiry study with the sciences processes skills affet learners’ biology from less to better with persentations of 36,67% and 63,33% each of those with conventional learning method. And after a test with analysis covariance a result of studying is less than 0,05 (α<0,05). This suggests that inquiry’s methods of study coupled with the science processes skills have an effect on students’ biology based on the structural materials and function of plant tissue.